2020
DOI: 10.3390/su12208550
|View full text |Cite
|
Sign up to set email alerts
|

Vegetation Dynamics and Their Response to the Urbanization of the Beijing–Tianjin–Hebei Region, China

Abstract: Rapid global urbanization has caused substantial changes in land cover and vegetation growth. Rapid urban growth in a short time has escalated the conflicts between economic development and ecological conservation, particularly in some metropolitan regions. However, the effects of rapid urbanization on vegetation have not been fully captured, especially accounting for the latest ecological development initiatives. In this study, we chose a typical urban agglomeration, the Beijing–Tianjin–Hebei (BTH) urban aggl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…This phenomenon can also be observed in developed countries such as Japan, the United Kingdom, and America [73]. The greening work in the area is getting better and better in the regions, which benefited from the urban park construction policy that Beijing has long persisted in [35,74]. In a word, proactive human activities play an important role in vegetation restoration [24,75].…”
Section: Driving Factors Of Vegetation Change In High and Low-intensi...mentioning
confidence: 90%
See 1 more Smart Citation
“…This phenomenon can also be observed in developed countries such as Japan, the United Kingdom, and America [73]. The greening work in the area is getting better and better in the regions, which benefited from the urban park construction policy that Beijing has long persisted in [35,74]. In a word, proactive human activities play an important role in vegetation restoration [24,75].…”
Section: Driving Factors Of Vegetation Change In High and Low-intensi...mentioning
confidence: 90%
“…Jiang M et al [34] calculated the fractional vegetation coverage by the method of dimidiate pixel model based on NDVI, which suggests that human activities are very significant factors to influence and explain the changes in Beijing and they are highly spatially heterogeneous from 2000 to 2015. Chang Y et al [35] considered that the response of vegetation to urbanization showed obvious differences and geographical heterogeneity in the urbanization gradient based on the nighttime light data. Nevertheless, these works do not continue into the latest year and quantify the role of human activities and climate factors in the process of vegetation restoration and degradation in Beijing.…”
Section: Introductionmentioning
confidence: 99%
“…The BTH region is characterized by the typical Monsoon Climate of Medium Latitudes, characterized by hot, rainy summers and cold, dry winters [54]. Cities within this region exhibit similar annual average humidity and precipitation (Table 1).…”
Section: Study Areasmentioning
confidence: 99%
“…Despite the socio-economic advantages brought by this swift urban growth, there is a growing concern about the adverse effects on the urban thermal environment, which poses health risks to the region's populous and affects the local ecosystem [56], [57]. Under the background of Coordinated Development of the BTH Region, the scale of urbanization in this region is expected to continue expanding [54], and this region is facing the risk of further deterioration in thermal environment conditions. Additionally, the BTH Region also faces an obvious imbalance in urban development, leading to varying degrees of urban heat environmental degradation across cities [58].…”
Section: Study Areasmentioning
confidence: 99%
“…Most of the southern plains are cultivated land and artificial urban vegetation. From the perspective of interannual changes, Chang et al [55] found a significantly enhanced vegetation growth in BTH region, with a strikingly spatial pattern of greening in the northwest and browning in the southeast from 2001 to 2018. Thus, the background vegetation status of the BTH urban agglomeration and the vegetation trends from 2001 to 2018 may be two main factors affecting the spatial heterogeneity of summer SUHI, which has also been verified in Gui et al [27].…”
Section: B Spatial Features Of the Summer Suhi In Bth Urban Agglomeration During 2001-2018mentioning
confidence: 99%